PENJADWALAN PERAWATAN PREVENTIVE PADA DRYER MACHINE DI DUEL LAUNDRY PANGKALPINANG - Arzela Tanjung Ampera; pristiansyah, S.ST.M.Eng; Tuparjono, S.ST.,M.T (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Machine dryers often have problems causing the temperature to not be hot, whether it's due to engine part damage or other things. As a result of these constraints the work was delayed. What happens is that the work is not optimal and results in losses. The goal is to reduce excess costs, simplify the work process for operators and also help business owners minimize sudden damage that results in sub-optimal performance. Preventive Maintenance is a maintenance and maintenance activity carried out to prevent the occurrence of unexpected damage symptoms and find conditions or circumstances that can cause production facilities to experience damage during the production process. In the ISMO method, there are several terms and stages that must be carried out to produce a scheduling system and determine cost estimates for the next few years. the results obtained are a manual checklist, soup for each machine and also a maintenance schedule for six and a half years and from the first six months of experimentation there has been a reduction in costs. Implementation of Preventive Maintenance scheduling on Duel laundry has been successful. From the comparison of time for six months. For development, research can be done by determining how many pieces of clothing will be processed to make it easier for workers to measure the capacity of the machine during operation.